AAnalisis Kinerja Windlass Di KR. Geomarin III Menggunakan Metode FMEA (Failure Mode Effect Analysis) - Nugraha, Fajar Bima Aji; Kusuma, I Putu Andhi Indira (Institut Teknologi Adhi Tama Surabaya, 2025)
Ship activities during the berthing process require an anchor to hold the ship and used to stretch and raise the anchor using a windlass. Optimal windlass performance greatly influences the overall operational efficiency of the ship. This research aims to analyze the performance of KR. Geomarin III windlasses in increasing operational efficiency, both in terms of time, cost and security. The method used in this research is Failure Mode Effect Analysis (FMEA). The research methodology includes collecting primary and secondary data through direct observation, interviews with the crew of Geomarin III. The windlass machine system at KR. Geomarin III is an electric power machine. Apart from that, there is a fishbone diagram to look for factors that cause possible failure of windlass performance on the ship. From the results of this research, 8 potential failure modes were obtained, then the 2 highest failure modes were obtained, in rank 1 the bad weather with an RPN value of 160 and rank 2 the engine did not start with an RPN value of 144. Windlass performance significantly contributes to increasing ship operational efficiency, but it needs to be done routine maintenance and monitoring system to ensure optimal performance in the future.